External trade and economic development in Nigeria : selected papers for the 1995 Annual Conference, the Nigerian Economic Society. - Nigerian Economic Society (Ibadan, Nigeria : The Nigerian Economic Society, 1995)
Conference papers and proceedings of the Nigerian Economic Society.
Includes bibliographical references.
oif 26/07/16 ; rua 14/11/16
Ref.
Keywords: Balance of payments; Commerce; Commercial policy; Economic history; Economic conditions -- 1970; Nigeria